Quantum-chemical simulation of radiation-induced destruction of starch - Litvyak, Vladimir; Atroshko, Mikhail; Shahab, Siyamak; Kravchenko, Vyacheslav; Batyan, Anatoly (Journal of the Belarusian State University. Ecology, 2023)
Exposure to native starch by ionizing radiation is a promising and environmentally safe technology for purposefully changing the physico-chemical properties of starch. The environmental friendliness of irradiated starch due to the possibility of its use in various spheres of human life. It can be a good sorbent of heavy metals and radioactive isotopes. In addition, irradiated starch can also be successfully used for technical purposes in various branches of the modern economic complex: pulp and paper industry, medicine, construction industry, woodworking, injection molding. Starch can act as a dietary fiber with probiotic properties and is able to be broken down by the enzyme systems of intestinal microorganisms, as well as actively participate in the process of intestinal peristalsis.The object of the study was the molecules formed in chemical reactions occurring during the radiation exposure of starch. It has been established that irradiation of polysaccharides reduces their melting point and rotation of the polarization plane, darkening is observed, and formaldehyde is formed. When irradiated with a dose of more than 150 kGy, the crystalline part of starch is damaged, its molecular weight and chain length decrease. When irradiated with a dose of more than 600 kGy, a decrease in the degree of starch polymerization is observed, which leads to a decrease in the specific viscosity of amylose and amylopectin. With an increase in the radiation dose, the solubility of starch in water increases. When irradiated, the sensitivity to enzymes changes andα-1→4 bonds are broken. The reducing ability increases in proportion to the radiation dose (starting from a dose of 10 kGy), the acidity of starch increases (the activator is oxygen), but decreases with increasing moisture. When starch is irradiated, fragments of polyoside chains of various lengths of partially degraded dextrins are formed, as well as radiolysis products (hydroxymethyl furfural, formalin, etc.). Free acids and esters are also formed, which hydrolyze at pH extremes, increasing acidity. Quantum chemistry methods have proved the fundamental possibility of the formation of free radicals in food starch and the possibility of their subsequent interaction with the polymeric chains of starch. The most stable conformers were found from the values of the total energy of the molecules, and their physicochemical and antioxidant properties were calculated.
Keywords: starch; radiation exposure; free radical; density functional theory